The Influence of Unemployment, Health, Education and Per Capita Income on the Number of Poor People in Bali Province - Dhisti Wafiq Fahira Hany; Kusuma, Hendra (Jurnal Ilmu Ekonomi JIE, 2024)
This study aims to determine the effect of unemployment, health, education, and per capita income on the number of poor people in Bali Province in 2018-2022. This study uses secondary data from the Central Bureau of Statistics of Bali Province. The data analysis technique used is panel data with the Common Effect Model approach. The results of the data analysis show that unemployment, health, elementary school education, high school education, college education, and per capita income significantly affect the number of poor people in Bali Province. In contrast, junior high school education does not significantly impact the number of poor people in Bali Province.